Evaluation of three strains of influenza A virus in humans and in owl, cebus, and squirrel monkeys. - Murphy, B R (1980)
The virulence of three cloned influenza A viruses was compared in humans and in three readily available species of nonhuman primates (owl, squirrel, and cebus monkeys) in an attempt to identify a species of monkey that could be used to investigate the genetic basis of attenuation of influenza A viruses for humans. Three influenza A viruses from two subtypes, i.e., the A/Udorn/72 (H3N2), A/Alaska/77 (H3H2), and A/Hong Kong/77 (H1H1) viruses, produced febrile influenzal illness in humans. Squirrel monkeys developed mild upper respiratory tract illness in response to each of the three viruses. Illness was accompanied by a high level of virus shedding; each of nine squirrel monkeys that shed equal to or greater than 10(5.0) 50% tissue culture infective doses of virus became ill, whereas those that shed less remained well. In contrast, the cebus and owl monkeys remained clinically well despite infection with each of the three viruses. Thus, squirrel monkeys appear to be moderately permissive primate hosts in which to investigate the genetic basis of virulence of human influenza A viruses.